Exploring temporal trends and disparities of Tuberculosis prevalence in Indonesia (2007–2023) - Nasution, Helmi Suryani; Syukri, Muhammad; Fitri, Adelina; Ningsih, Vinna Rahayu (Proceedings Academic Universitas Jambi, 2025)
Background: Tuberculosis (TB) remains a major public health challenge globally, and Indonesia continues to be among the countries with the highest TB burden. Despite progress in TB control, limited studies have examined long-term trends and regional disparities using repeated nationally representative surveys. Objective: This study aimed to analyze temporal trends and geographic disparities of TB prevalence in Indonesia between 2007 and 2023. Methods: This study employed a cross-sectional design using secondary data from the Indonesian National Basic Health Research (Riskesdas) surveys conducted in 2007, 2013, and 2018, and the Indonesian Health Survey (SKI) conducted in 2023. TB prevalence was defined based on self-reported diagnosis by healthcare professionals within one year prior to the survey. Descriptive and exploratory analyses were performed to assess changes over time and across demographic and regional groups. Results: TB prevalence demonstrated a general downward trend from 2007 to 2023, with a temporary increase observed in 2018. The decline was more evident among females and urban residents, whereas higher prevalence persisted among males, older adults, and those in urban areas. Substantial interprovincial disparities were also observed, with provinces outside Java showing consistently higher prevalence. Conclusion: Although overall TB prevalence in Indonesia has declined, persistent demographic and regional inequalities remain. These findings highlight the need for targeted, area-specific interventions and strengthened surveillance systems to support progress toward national and global TB elimination goals.